Effect of Calcium Polysulfide Applications on Severity of Cocoa Pod Rot (Phytophthora palmivora Butl.) and Fungal Diversity - Widiyasmoro, Wahyu; Martosudiro, Mintarto; Sulistyowati, Liliek (The Journal of Experimental Life Science, 2017)
Indonesian government gives a high priority for the development and revitalization of cocoa production. In 2012/2013, production of cocoa in Indonesia reached 410,000 ton from 1,774,500 ha (about 231 kg ha-1), lower than Ghana which is 835,000 ton from 1,600,300 ha (about 521 kg ha-1). One of the constraints of cocoa production in Indonesia is pod rot disease caused by Phytophthora palmivora, which can reduce about 90% of production during wet season. Calcium polysulfide was suggested as one of the potential, cheap and save substance to control P. palmivora. The purpose of this study was to evaluate the calcium polysulfide potential to control the disease and its effect on the phyllosphere-fungal diversity. A positive correlation was found between concentration of calcium polysulfide and inhibition of fungal growth in the media. Otherwise, a negative correlation was found between concentration of calcium polysulfide and fungal biomass. Disease severity of cocoa treated by calcium polysulfide 80 mL L-1 every weekÂ was 11.67% significantly lower than control, i.e. 68.33%. Furthermore, it was also found that the index value of fungal diversity on the phylosphere decreased by increasing concentration and interval ofÂ  calcium polysulfide application.Keywords: Calcium polysulfide, Cocoa, Phytophthora palmivora.